2020
DOI: 10.17509/jsl.v3i2.20796
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Investigation of the Views of Preschool Teachers and Teacher Candidates about STEM

Abstract: If the STEM approach appropriately addressed in early childhood education, it may provide opportunities for educators to involve children in activities appropriate to their interests and experiences. The purpose of this research is to investigate comparatively the views of preschool teachers and preschool teacher candidates about STEM. To collect data, 60 preschool teachers graduated from different universities in Turkey have different experiments and actively in the teaching profession in various schools in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
(18 reference statements)
2
15
0
2
Order By: Relevance
“…But most students like mathematics learning that is integrated with science and technology because they think learning to be relaxed like a play. This result is in line with previous research which states that by integrating mathematics learning with science, the connection of knowledge to concepts across disciplines and their application to the real world becomes easier for students to understand (Honey et al 2014;Johnson et al 2015;Kelley & Knowles, 2016;Thibaut et al 2018;Uğraş & Genç, 2018;Ültay & Ultay, 2020).…”
Section: Figure 1 Student Portfoliossupporting
confidence: 92%
“…But most students like mathematics learning that is integrated with science and technology because they think learning to be relaxed like a play. This result is in line with previous research which states that by integrating mathematics learning with science, the connection of knowledge to concepts across disciplines and their application to the real world becomes easier for students to understand (Honey et al 2014;Johnson et al 2015;Kelley & Knowles, 2016;Thibaut et al 2018;Uğraş & Genç, 2018;Ültay & Ultay, 2020).…”
Section: Figure 1 Student Portfoliossupporting
confidence: 92%
“…This result is compatible with the other studies in the literature. It is stated in these studies that information technologies, science, preschool and elementary education teachers have positive attitudes towards STEM (Çevik, Danıştay, & Yağcı, 2017;Karahan, Canbazoğlu Bilici, & Ünal, 2015;Knop et al, 2017;Ültay & Ültay, 2020). It was stated that in this research, some studies found STEM education effective at improving learning by doing, making learning permanent, directing research and inquiry, in the development of problem solving skills, making learning enjoyable, and being successful in learning subjects.…”
Section: Discussionmentioning
confidence: 80%
“… Shen et al (2021) stated that students can develop higher-order thinking as well as competency-based literacy in STEAM activities. Furthermore, Ültay and Ültay (2020) stated that teacher education students are considered an important group for educational sustainability and that engaging in more STEAM activities can help them acquire 21st century skills such as collaboration and innovation. More importantly, related studies have also found that learners with higher learning performance in inquiry-based learning activities tend to have higher inquiry behaviors and continue to improve their scientific literacy in inquiry settings ( Wen et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…STEAM education, on the other hand, is a multidisciplinary approach that emphasizes the development of higher-order thinking and competencies ( Shen et al, 2021 ), with more emphasis on hands-on activities that promote the development of sustainable inquiry behaviors ( Rahmawati et al, 2022 ). In addition, in the process of educational sustainability, teacher education students need to promote the development of their collaborative, creative, and thinking skills through STEAM learning ( Ültay and Ültay, 2020 ), and to improve their learning performance through course work that better promotes continuous inquiry behaviors. That is, students with higher academic achievement tend to have higher inquiry behaviors and, conversely, students with lower academic achievement tend to have lower inquiry behaviors ( Chen and Wang, 2020 ).…”
Section: Research Hypothesis and Modelmentioning
confidence: 99%
See 1 more Smart Citation